Larvae and females of two Stenopsyche species in Taiwan with redescription of the male of S. formosana (Insecta: Trichoptera) - Nozaki, Takao; Saito, Rie; Nishimura, Noboru; Hsu, Li-Peng; Tojo, Koji (Zootaxa, 2016)
Larvae and females of two Stenopsyche species, S. formosana Kobayashi and S. drakon Weaver, are described for the first time. They were associated with the adult male through mitochondrial DNA sequence comparisons. The male of S. formosana, which has been recorded as Stenopsyche banksi Mosely from Taiwan, is redescribed. The males of S. formosana and S. banksi can be distinguished from each other by the shape of segments IX and X, and endothecal spines. In larvae, S. formosana and S. drakon are distinguishable from each other and from other known species by the combination of different dark marking patterns and shapes of no. 18 setae of the head, and by the shapes of forecoxae. The larval morphology of S. formosana and S. drakon suggests that the phylogenetic relationships based mainly on male genitalia in the genus Stenopsyche should be reconsidered.